ORGANIZATIONAL CLIMATE AND PROFESSIONALISM IN PUBLIC SERVICE - Harries Madiistriyatno; Enjang Sudarman (Jurnal Ekonomi, 2022)
The provision of adequate public services to the community requires solidity within the organization. Efforts to realize this solidity can be done, among others, by building a good organizational climate and upholding professionalism. This study aims to analyze the effect of organizational climate and professionalism on the performance of sub-district employees in providing public services to the community. The study involved three variables: organizational climate, professionalism, and employee performance. The questionnaire used to collect data was distributed to 39 respondents and processed with the help of SPSS 22. Hypothesis testing was carried out by t-test and F-test to determine the effect between variables, either partially or simultaneously. The influence of organizational climate and professionalism on employee performance is positive either partially or simultaneously, with a contribution of 73.3% overall. Based on research findings, organizational climate and professionalism have been shown to affect employee performance either partially or simultaneously.